Hypertensive crisis induced acute pulmonary edema in emergency care unit Sumbawa hospital: a case report - Syammakh, Muhammad Ahmad; Anthonius, Franky Renato (International Journal of Research in Medical Sciences, 2018)
Acute cardiogenic pulmonary edema is a common cause of respiratory distress in emergency department (ED) patients. Pulmonary edema is a problem of major clinical importance resulting from a persistent imbalance between forces that drive water into the air space of the lung and the biological mechanisms for its removal. A patient 66 years old female, with a history hypertency stage II and osteoarthritis admitted to emergency department with acute pulmonary edema. On evaluation, the patient had intense dyspnoe, agitated, diaphoresis without cyanosis, the pulse pressure was normal, rapid and regular. Noninvasive ventilation by noninvasive positive pressure ventilation or continuous positive airway pressure has been studied as a treatment strategy. Noninvasive ventilation and intravenous nitrates are the mainstay of treatment which should be started within minutes of the patient’s arrival to the ED. Use of morphine and intravenous loop diuretics, although popular, has poor scientific evidence. We critically evaluate the evidence for the use of noninvasive ventilation on rates of hospital mortality and endotracheal intubation. Although is often results from atrial fibrillation, acute myocardial infarction, hypertension crisis, discontinuation of medication edema. It is important to understand this disease, rapid diagnostic with ultrasound and when treated promptly and effectively, these patients will rapidly recovery. Good oxygenation, intravenous nitrates, intravenous diuretics and low dose sedation which should be started within minutes of the patients arrival to emergency department.